Narratividad y memoria. Hacia una ética de la responsabilidad. - Rovaletti, María Lucrecia (Salud Mental)
Prisoners of the Nazi concentration camps explained that the necessity to count all that horror stayed with them in life. In this moment, they were founding an “ethics of the testimony", that is to say, the salvation of the victims by means of their memory. Indeed Ricoeur shows that "time becomes human time in the measurement in which it is articulated in a narrative way". In this sense, he points out that narrative plots constitute "the privileged means by which we form our confused, shapeless and, at limit, dumb, temporary experience". In spite of that, experience not always reaches to being object of a story. Sometimes, the traumatic experience prevents the individual from taking control of his/her personal history. There is a strong temptation to deny that this experience has taken place, or it is lived as if it happened to another person. In those "dark nights" of the soul, in those moments of extreme dispossession, «the question of "who am I" does not refer to the nullity, but it refers to the same nudity of the question» (Ricoeur). For that reason, so that it is not an unbearable sequence of events, we narrated a story and we looked for its meaning. We do not do it to forgive or to forget, but to obtain "the privilege to judge". If the oblivion leads to a break from tradition, the truth however is not "a discovery that destroys the secret, but the disclosure that makes justice to it and allows to be passed on to the future generations" (Arendt).